Analysis of Financial Ratios of PT Industri Jamu and Farmasi Sido Muncul TBK (Sido) for the Period of 2018-2020 - Michellia Maitri Ratana (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this study is to find out the financial performance of PT Industri Jamu dan Farmasi Sido Muncul Tbk in the 2019-2023 period to see what the Company's capabilities are like using financial ratio analysis. This research uses secondary data such as financial statements and company reports. The analysis tools used in this study are liquidity ratio, activity ratio, solvency ratio and profitability ratio. Based on the results of this study, PT Industri Jamu dan Farmasi Sido Muncul Tbk in the 2019-2023 period experienced fluctuations in its ratio value. Especially in 2020-2021, the results of the calculation of the liquidation ratio in 2020 experienced a significant decrease compared to the previous year. Meanwhile, the solvency ratio increased in 2020 and gradually decreased in the following years. Similar to the solvency ratio, the value of the profitability ratio also experienced a significant increase in 2020-2021. For the calculation of the activity ratio, the value of Total Asset Turnover, in the 2019-2023 period, no one has reached the existing industry standard figure of 5 times, resulting in the Company being in a bad position. However, for the calculation of other ratio values, despite fluctuations affected by the Covid-19 pandemic in 2020-2021, the Company's ratio value is still in a good position because it is still above industry standards.